Pericyte Loss Leads to Capillary Stalling Through Increased Leukocyte-Endothelial Cell Interaction in the Brain - Choe, Young-Geun; Yoon, Jin-Hui; Joo, Jongyoon; Kim, Bokyung; Hong, Seon Pyo; Koh, Gou Young; Lee, Dong-Seok; Oh, Wang-Yuhl; Jeong, Yong (Frontiers in Cellular Neuroscience, 2022)
The neurovascular unit is a functional unit composed of neurons, glial cells, pericytes, and endothelial cells which sustain brain activity. While pericyte is a key component of the neurovascular unit, its role in cerebral blood flow regulation remains elusive. Recently, capillary stalling, which means the transient interruption of microcirculation in capillaries, has been shown to have an outsized impact on microcirculatory changes in several neurological diseases. In this study, we investigated capillary stalling and its possible causes, such as the cerebral endothelial glycocalyx and leukocyte adhesion molecules after depleting pericytes postnatally in mice. Moreover, we investigated hypoxia and gliosis as consequences of capillary stalling. Although there were no differences in the capillary structure and RBC flow, longitudinal optical coherence tomography angiography showed an increased number of stalled segments in capillaries after pericyte loss. Furthermore, the extent of the cerebral endothelial glycocalyx was decreased with increased expression of leukocyte adhesion molecules, suggesting enhanced interaction between leukocytes and endothelial cells. Finally, pericyte loss induced cerebral hypoxia and gliosis. Cumulatively, the results suggest that pericyte loss induces capillary stalling through increased interaction between leukocytes and endothelial cells in the brain.